Detection and quantification of pesticide residues in tomatoes sold in urban markets of Ouagadougou, Burkina Faso - Dione, Michel Mainack; Djouaka, Rousseau; Mbokou, Serge Foukmeniok; Ilboudo, Guy Sidwatta; Ouedraogo, Abdoul Aziz; Dinede, Getachew; Roesel, Kristina; Grace, Delia; Knight-Jones, Theodore J. D. (Frontiers in Sustainable Food Systems, 2023)
Introduction “What people worry about, and what makes them sick and kills them, are not the same” is maxim for risk communication experts. In Burkina Faso, pesticides are used by vegetable producers to improve productivity. However, consumer concern over pesticide use is high. Of course, if over-used pesticides could have serious health consequences for producers and consumers and also cause ecological damage. Methods A cross-sectional survey was conducted to detect and quantify the levels of residues of pesticides in tomatoes sold in urban markets of Ouagadougou. Two samples were collected from each vendor (n = 328 vendors) making a total of 656 tomato samples from 26 markets. Samples were subjected to High-Performance Liquid Chromatography (HPLC) for detection and quantification of six pesticide residues commonly used in West Africa including acetamiprid, chlorpyrifos, lambda-cyhalothrin, deltamethrin, dichlorodiphenyltrichloroethane (DDT), and permethrin. Results Overall, 62.2% of tomato samples contained at least one pesticide residue including acetamiprid, chlorpyrifos, lambda-cyhalothrin and DDT. Deltamethrin and permethrin were however not detected in any samples. The highest proportions of samples were contaminated with DDT (32.9, 95%CI: 27.9–38.3%), followed by acetamiprid (31.1, 95%CI: 26.2–36.5%), lambda-cyhalothrin (28.4, 95%CI: 23.6–33.6%) and chlorpyrifos (10.7, 95%CI, 7.6–14.6%). 21.3% of samples exceeded Codex Alimentarius Commission (CAC) Maximum Residue Levels (MRLs) including Acetamiprid (13.1%), DDT (7.3%), lambda-cyhalothrin (2.1%) and chlorpyrifos (0.3%); while 61.3% of sample exceeded European Union (EU) MRLs. Multiple pesticide residues (up to 4) were detected simultaneously in 27.7% of the total samples. Conclusion The study suggests that producers and consumers may be exposed to pesticides that can be highly toxic to them and to the environment. We recommend further quantitative risk assessment for consumer exposure and identification of best procedures to reduce residues in vegetables. Meanwhile, monitoring and regulating pesticide use, with the promotion of good agricultural practices, are warranted to prevent consumers, producers and environmental exposure. However, given this may not be effective, promotion of consumer washing and peeling of vegetables may be warranted to at least empower consumers to protect themselves. Moreover, where resources are scarce they should be directed to the highest burden hazards and in Burkina Faso, these are not likely to be pesticides.